Uji Aktivitas In Vivo Antinosiseptif Kombinasi Ekstrak Daun Dandang Gendis [Clinacanthus nutans (Burn F) Lindau] dan Daun Bakung (Crinum asiaticum L) - Essty Damayanti; Chaidir Chaidir; Rachmaniar Rachmat (Faculty of Pharmacy, Universitas Muslim Indonesia, 2021)
Almost all diseases in the body cause pain. Currently the most widely used analgetic has not regardless from side effects. The development of new and effective pain medications that are natural is expected to have the benefits of treatment. 75% ethanol extract of dandang gendis leaf (Clinacanthus nutans (Burn F) Lindau) dosage 279,3 mg/kg BW and 96% ethanol fraction of bakung leaf (Crinum asiaticum) dosage 250 mg/kg BW were shown to have antinociceptive activity. The purpose of this study was to determine the antinociceptive effectiveness of a combination of 75% ethanol extract from dandang gendis leaves and 96% ethanol fraction of bakung leaf. In this study was used chemical method induction (Sigmund's method) in 25 male mice which were divided into 5 treatment groups, namely treatment group I as negative control was given CMC 0.5%, treatment group II as positive control was given acetosal 100 mg / kg BW, treatment groups III, IV and V were given combinationsextract. Each group was given treatment orally, thirty minutes then induced with 0.6% acetic acid intraperitonially, after which it was observed and counted for the amount of stretching for sixty minutes. Data were analyzed by one-way ANOVA to see differences in antinociceptive effects in each treatment group. The results of this study showed that all treatment groups had a significant difference (p <0.05), the combination of 75% ethanol extract dandang gendis leaf and 96% ethanol fraction of bakung leaf with a dose of 100 mg / kg BW had good effectiveness with a percent effectiveness value of 92.50%. The results of this study indicate that the combination of 75% ethanol extract from dandang gendis leaf (Clinacanthus nutans (Burn F) Lindau) and 96% ethanol fraction from bakung leaf (Crinum asiaticum) with the same concentration ratio, have relatively higher antinociceptiveof the activity of each extract, in other words both of them work together.